Nervonic acid as novel therapeutics initiates both neurogenesis and angiogenesis for comprehensive wound repair and healing - Liu, Yu-Da; Peng, Xiao; Chen, Hao-Ran; Liu, Xue-Song; Peng, Li-Hua (Frontiers in Pharmacology, 2024)
Rapid tissue reconstruction in acute and chronic injuries are challengeable, the inefficient repair mainly due to the difficulty in simultaneous promoting the regeneration of peripheral nerves and vascular, which are closely related. Main clinical medication strategy of tissue repair depends on different cytokines to achieve nerves, blood vessels or granulation tissue regeneration, respectively. However, their effect is still limited to single aspect with biorisk exists upon long-time use. Herein, for the first time, we have demonstrated that NA isolated from Malania oleifera has potential to simultaneously promote both neurogenesis and angiogenesis in vitro & in vivo. First, NA was identified by NMR and FTIR structural characterization analysis. In a model of oxidative stress in neural cells induced by hydrogen peroxide, the cells viability of RSC96 and PC12 were protected from oxidative stress injury by NA. Similarly, based on the rat wound healing model, effective blood vessel formation and wound healing can be observed in tissue staining under NA treatment. In addition, according to the identification of nerve and vascular related markers in the wound tissue, the mechanism of NA promoting nerve regeneration lies in the upregulation of the secretion NGF, NF-200 and S100 protein, and NA treatment was also able to up-regulate VEGF and CD31 to directly promote angiogenesis during wound healing. This study provides an important candidate drug molecules for acute or chronic wound healing and nerve vascular synchronous regeneration.